Da utopia ao desencanto e do desencanto à esperança: impressões de profissionais da estratégia saúde da família à luz da história oral - Santana, Gicélia Maria Simplício de (2010)
In 1994, Campina Grande-PB was one of the first municipalities in Brazil to implement the Family Health Program. Years later became the Family Health Strategy to be recognized as important for the construction of a new model of health care from the reorganization of primary care services. This study aimed to reveal the impressions of professional pioneers of the Family Health Program in Campina Grande, in the light of oral history. This is a qualitative research method was used to oral history. Participated as ten professional staff, top-level teams of five members of the pioneering Family Health Program in Campina Grande-PB. After Corpus analysis four themes emerged: The pioneering teams and the hope of realizing the SUS by the family health strategy; The development of the PSF in Campina Grande - 1994 to 2006; PT management in the health and viability of the Health Family as a model of attention, desires, achievements and limitations; The Family Health Strategy after PT management: from disillusionment to hope. Through the analysis it was observed that the pioneer group of Family Health of Campina Grande had the brand of militancy in defense of the NHS and the principles of health reform, coupled with political and ideological training. Chasing the utopia of turning into a family health care model. This hope was strengthened by the reversal of some epidemiological indicators. In the second main theme was possible to recognize an intense mobilization of professionals. With his performance created the Association of Professional Family Health of Campina Grande, implanted the local health councils and built expectations of achieving social rights arising from social pressure. The strengthening of the category could be in parallel with the conflict with the managers on behalf of Family Health. These conflicts directly involved managers who just showed up prepared and knowledgeable family health project. In the third thematic area it was found that the entry of a health worker in the office of secretary of health professionals had revitalized their hopes of advancing to the Family Health and SUS. Despite advances employees show the limits of the management PT. The fourth theme is the cooling of the class forces, the dismantling of the professionals and significant decrease of the coping capacity of local government. After more than a decade of struggle employees express disenchantment with the current health management. However, most appear to be hopeful about the progress of SUS and Family Health. In designing a new health history in the city expects to rely on the strength of the new professionals working in family health teams and with the support of the population.